Development of insectarium media combined with QR code on animalia subject for the ten-grade students - Fakhirah Maulidya; Zulkarnaim Zulkarnaim; Ainul Uyuni Taufiq (JPBIO (Jurnal Pendidikan Biologi), 2023)
Insectarium media combined with QR code referred to this research was learning media based of technology created that can also be used on smartphone. This research aims to develop learning media and determine students’ response to insectarium combined with QR code that appropriate to be used as learning media in the kingdom Animalia. The method used is research and development with a design ADDIE model which consists of five stages in the form of analyzing, design, develop, implement, and evaluate. Research subjects is the ten-grade students who took animalia’s' kingdom courses, the academic year 2021/2022 of the SMA Negeri 02 Bombana. The research instrument used was validation questionnaire, test items, students and teacher questionnaire. The result of insectarium combined with QR code validity level got 3.76 score as a very valid categorize from the material and design experts, the effectiveness level got very effective categorized by 89% percentage, the practically level by students and the teacher response is 89.83% categorized as very practical. The result obtained it was concluded that insectarium combined with QR code was suitable for use as a medium in school and there needs to be implemented to see achievement.